Formación Y Desempeño Profesional Del Ingeniero Agropecuario Graduado En La Facultad De Ciencias Agropecuarias De La Universidad Técnica De Babahoyo En El Quinquenio 2009 – 2014. - Idrovo Gurumendi Mercy Verónica (2015)
This research work has as interest the study of the formation and performance of agricultural engineers, their expectations regarding the proposed reflected in the coordinated development of the process of this company scenario; so it may be affected by social, economic and cultural changes in the environment in which it is not intended to eliminate what is done within the Faculty of Agricultural Sciences at the level of the curriculum if not propose solutions to the elements that generate them. From a critical perspective aims to identify the following problem What are the factors affecting the formation and professional performance of Agricultural Engineer graduated from the Faculty of Agricultural Sciences, Technical University of Babahoyo in the year 2009 - 2014 ?, this study will review the curriculum with which they were enrolled in their levels of study, the level of theoretical knowledge - practical with which they were undertaken in the workplace, considered then that this analysis assumes the essential logic of the profession and methods that characterize which was applied in a representative population respectively graduates and administrative Faculty of Agricultural Sciences at the Technical University of Babahoyo. Being one of the main goals of education, training and professional development is necessary to develop a method that may lead us to excellence and one of the main goals is that the engineer will play in their specialty, because that's where it performs competitiveness in their career within a participatory and ongoing process.